J/[psi] production cross section and its dependence on charged-particle multiplicity in p+p collisions at √s=200 GeV - Adam, Jaroslav; Deppner, Ingo Martin; Herrmann, Norbert (Physics letters, 2018)
We present a measurement of inclusive J/ψ production at mid-rapidity (|y|<1) in p+p collisions at a center-of-mass energy of s=200 GeV with the STAR experiment at the Relativistic Heavy Ion Collider (RHIC). The differential production cross section for J/ψ as a function of transverse momentum (pT) for 0<pT<14 GeV/c and the total cross section are reported and compared to calculations from the color evaporation model and the non-relativistic Quantum Chromodynamics model. The dependence of J/ψ relative yields in three pT intervals on charged-particle multiplicity at mid-rapidity is measured for the first time in p+p collisions at s=200 GeV and compared with that measured at s=7 TeV, PYTHIA8 and EPOS3 Monte Carlo generators, and the Percolation model prediction.